Risiko dalam Implementasi Free On Board (FOB) Berdasarkan Incoterms 2010 pada Penyelenggaraan Pengangkutan Laut - Zefanya, Anastasia; Trisnamansyah, Purnama; Maulana, Mursal (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
Incoterms 2010, issued by the International Chamber of Commerce and effective January 1, 2011, is a set of rules for the delivery of products between sellers and buyers that are routinely included in international sales contracts. Incoterms 2010 provides harmonized rules of interpretation for eleven general trading terms. From these eleven common terms, a trader must select the Incoterms that are most appropriate for the specific transaction he wishes to undertake. If used correctly, Incoterms 2010 is an effective risk management tool. However, old trading practices create tensions with modern transportation practices and Incoterms 2010, potentially increasing risks for traders. When using Incoterms, Free On Board (FOB) terms are the most frequently used in transportation methods. This article intends to examine what risks occur in using the term FOB, especially in sea transportation. The type of research used in this paper is normative legal research (normative analysis) using library materials as a source of research data. Furthermore, this article intends to provide support to traders to learn more about FOB so that they can propose criteria that might be applied to choose the most appropriate Incoterm. Therefore, this will be the basis of how the mode of transport influences and sometimes even determines choices for a certain period of time.